2020
DOI: 10.1158/1078-0432.ccr-20-1315
|View full text |Cite
|
Sign up to set email alerts
|

The XPO1 Inhibitor KPT-8602 Synergizes with Dexamethasone in Acute Lymphoblastic Leukemia

Abstract: is a second generation exportin-1 (XPO1) inhibitor with potent activity against acute lymphoblastic leukemia (ALL) in pre-clinical models and with minimal effects on normal cells. In this study, we evaluated if KPT-8602 would synergize with dexamethasone, vincristine or doxorubicin, three drugs currently used for the treatment of ALL. Experimental designFirst, we searched for the most synergistic combination of KPT-8602 with dexamethasone, vincristine or doxorubicin in vitro in both B-ALL and T-ALL cell lines … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…CRM1 specific inhibitors are being used in clinical trials as a target for number of cancer therapies including non-Hodgkin lymphomas ( [63,64] and reviewed in [65,66]). Of interest, a CRM1 inhibitor showed anticancer activity in a JAK3 mutant mouse model for T-ALL [67,68] suggesting the highly interesting possibility that shifting the dynamics of nuclear import/export and the balance between nuclear and cytoplasmic JAK3 might also be a novel potential target for therapy in CTCL. Accordingly, CRM1 inhibitors could be of interest to test as novel remedies for inhibition of malignant T cells in CTCL as it regulates the activity of JAK3/STAT3/SOCS3, a key signaling pathway in malignant transformation in CTCL [17].…”
Section: Discussionmentioning
confidence: 99%
“…CRM1 specific inhibitors are being used in clinical trials as a target for number of cancer therapies including non-Hodgkin lymphomas ( [63,64] and reviewed in [65,66]). Of interest, a CRM1 inhibitor showed anticancer activity in a JAK3 mutant mouse model for T-ALL [67,68] suggesting the highly interesting possibility that shifting the dynamics of nuclear import/export and the balance between nuclear and cytoplasmic JAK3 might also be a novel potential target for therapy in CTCL. Accordingly, CRM1 inhibitors could be of interest to test as novel remedies for inhibition of malignant T cells in CTCL as it regulates the activity of JAK3/STAT3/SOCS3, a key signaling pathway in malignant transformation in CTCL [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these drugs also potently inhibited cluster A cancers, revealing general YAP off selectivity (Figures 4F and S4D). Notably, aurora kinase inhibitors are synthetic lethal with RB1 loss (Gong et al, 2019;Oser et al, 2019), which is enriched in YAP off solid cancers (Figure 3E), and XPO1 and BCL or HDAC inhibitors are potent against leukemia and SCN tumors, respectively (Balanis et al, 2019;Verbeke et al, 2020). We validated several YAP off -selective drugs, and expressing YAP and/or constitutively active YAP S5A reduced sensitivity in several YAP off cancer types (Figures 4G and 4H).…”
Section: Yap/taz and Integrin/adhesion Genes Stratify Binary Pan-cancer Classesmentioning
confidence: 99%
“…Similarly, imatinib could be used for rare T-ALL cases with ABL1 fusions, but case reports have shown variable efficacy in this setting [18] . Recently, selective inhibition of nuclear export by the second-generation exportin-1 (XPO1) inhibitor KPT-8602 (eltanexor) was shown to induce apoptosis in various cancer types, including ALL [19 , 20] , without deleterious effects to normal hematopoiesis [21] . Interestingly, the cancer-specific properties of this small molecule do not require specific mutations and previous studies in ALL have shown a general sensitivity of ALL cells for KPT-8602, independent of any genomic markers [19 21] .…”
Section: Introductionmentioning
confidence: 99%